Analysis of Transformational Leadership and Organizational Communication on Employee Performance with Organizational Commitment as A Mediating Variable at The Medan Belawan Primary Tax Office Medan Belawan Primary Tax Service Office - Aditya Muchtar; Elfitra Desy Surya; Erwansyah Erwansyah (Jurnal Fokus Manajemen, 2026)
Employee performance is a strategic factor in supporting the achievement of public organization goals, especially in tax agencies that have high performance demands. This study aims to analyze the influence of transformational leadership and organizational communication on employee performance with organizational commitment as a mediating variable at the Medan Belawan Primary Tax Office. This study uses a quantitative approach with a survey method. The population in this study was all 100 permanent employees of the Medan Belawan Tax Office, all of whom were used as research samples. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the help of SmartPLS software. The results showed that transformational leadership and organizational communication had a positive and significant effect on employee performance. In addition, transformational leadership and organizational communication also have a positive and significant effect on organizational commitment. Organizational commitment has been proven to have a positive and significant effect on employee performance. Furthermore, the results of the indirect effect test show that organizational commitment is able to significantly mediate the effect of transformational leadership and organizational communication on employee performance. The coefficient of determination shows that transformational leadership and organizational communication can explain 56.8% of the variation in employee performance. The findings of this study indicate that improving employee performance at the Medan Belawan Tax Office can be achieved by strengthening the role of transformational leadership, improving the quality of organizational communication, and increasing employee commitment to the organization. The results of this study are expected to provide practical contributions to tax agency leaders in formulating sustainable human resource management policies.